To Digital or not to Digital: How Mothers are Navigating the Digital World with their Young Children - Laura Teichert (Language and Literacy: A Canadian Educational e-journal, 2017)
We know many children are using digital tools, such as mobile phones and tablets. Much has been debated about the appropriateness of these tools in the lives of young children (e.g., American Academy of Pediatrics, 2001, 2011; National Association for the Education of Young Children, 2012). Yet, parents are engaged in digital practices. Adults’ beliefs about the appropriateness of digital media for children influence the environments they create for young children and potentially influence children’s exposure to and interactions with digital tools. This paper describes the digital literacy practices of three families and reports on the tensions mothers felt in whether to allow their children to participate in these practices.